Application of Evolutionary Algorithms and Statistical Analysis in the Numerical Optimization of an Axial Compressor - Alberto Clarich; Giovanni Mosetti; Valentino Pediroda; Carlo Poloni (International Journal of Rotating Machinery)
The purpose of this work is to optimize the stator shape of an axial compressor, in order to maximize the global efficiency of the machine, fixing the rotor shape. We have used a 3D parametric mesh and the CFX-Tascflow code for the flow simulation. To find out the most important variables in this problem, we have run a preliminary series of designs, whose results have been analyzed by a statistic tool. This analysis has helped us to choose the most appropriate variables and their ranges in order to implement the optimization algorithm more efficiently and rapidly. For the simulation of the fluid flow through the machine, we have used a cluster of 12 processors.